Amides Derived from Vanillic Acid: Coupling Reactions, Antimicrobial Evaluation, and Molecular Docking. (15th April 2019) - Santos Oliveira, Ana Júlia de Morais; de Castro, Ricardo Dias; Pessôa, Hilzeth de Luna Freire; Wadood, Abdul; de Sousa, Damião Pergentino
Abstract : A series of amides derived from vanillic acid were obtained by coupling reactions using PyBOP ((Benzotriazol-1-yloxy)tripyrrolidinophosphonium hexafluorophosphate) and DCC (Dicyclohexylcarbodiimide) coupling reagents. These were submitted to biological evaluation for species of Candida, Staphylococcus, and Pseudomonas . The microdilution method in broth was used for the antimicrobial testing to determine the Minimum Inhibitory Concentration (MIC) and to verify the likely mechanism of action for antifungal activity. The ten amides were obtained with yields ranging from 28.81 to 86.44%, and three compounds were novel. In the antibacterial evaluation, the amides (in their greatest concentrations) were bioactive against Staphylococcus aureus strain ATCC 25925. Meanwhile, all of the tested amides presented antifungal activity against at least one strain. The amide with best antifungal profile was compound7, which featured an MIC of 0.46 μ mol/mL, and a mechanism of action involving the plasma membrane and fungal cell wall. The presence of a methyl group in the para position of the aromatic ring is suggested which enhances the activity of the compound against fungi. Docking studies of the ten compounds using the protein 14 α -demethylase as a biological target were also performed. The biological results presented good correlation with molecular docking studies demonstrating that a possible site of antifungal action for bioactive amides is the enzyme 14 α -demethylase.